2002
DOI: 10.1038/oby.2002.55
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TNF‐α−308 G/A Promoter Polymorphism with Insulin Resistance in Obesity

Abstract: 2002;10:401-407. Objective: Obesity is a major risk factor for the development of type 2 diabetes. Tumor necrosis factor (TNF)-␣ is a candidate gene for the development of both obesity and insulin resistance. We investigated whether a common polymorphism in the promoter region (Ϫ308 G/A) of the TNF-␣ gene was associated with increased risk for the development of insulin resistance and cardiovascular disease in an obese Australian population. Research Methods and Procedures: Obese, non-diabetic subjects (146 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
4
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 35 publications
5
87
4
7
Order By: Relevance
“…Finally, a common polymorphism in the promoter region of the TNF-a gene has been associated to increased TNF-a and systolic BP. 35 Contrary to previous studies aimed to test this hypothesis, 6,7,36 we did not find a significant association between CRP and hypertensive status. In our analysis the effect of CRP may be absent due to the inclusion of TNF-a and IL-6 in the final model.…”
Section: Discussioncontrasting
confidence: 97%
“…Finally, a common polymorphism in the promoter region of the TNF-a gene has been associated to increased TNF-a and systolic BP. 35 Contrary to previous studies aimed to test this hypothesis, 6,7,36 we did not find a significant association between CRP and hypertensive status. In our analysis the effect of CRP may be absent due to the inclusion of TNF-a and IL-6 in the final model.…”
Section: Discussioncontrasting
confidence: 97%
“…Indeed, gene polymorphisms of TNF have been associated with obesity by many investigators. [24][25][26][27][28][29][30][31] Infiltrative macrophages have been shown to be increased and to be the main source of TNF-a expression in adipose tissue in obese mice. 32,33 MIF could upregulate TNF-a secretion by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…104,105 Some, but not all studies, have indicated a key role for the À308 variant of the TNF gene in the pathogenesis of obesity and obesity-associated insulin resistance. [57][58][59][106][107][108][109][110][111] However, only four of these studies include anthropometric indices of central obesity. 57,58,110,111 Among these studies, two reported associations between the GÀ308A variant of the TNF and measurements of central obesity.…”
Section: Tumor Necrosis Factor Gene (Tnf)mentioning
confidence: 99%
“…[57][58][59][106][107][108][109][110][111] However, only four of these studies include anthropometric indices of central obesity. 57,58,110,111 Among these studies, two reported associations between the GÀ308A variant of the TNF and measurements of central obesity. 57,58 In one of the negative studies, men homozygous for the A allele had a trend toward greater central adiposity and higher insulin and glucose levels.…”
Section: Tumor Necrosis Factor Gene (Tnf)mentioning
confidence: 99%
See 1 more Smart Citation